OP0011 Derivation of a biobank of pancreatic ductal adenocarcinoma xenografts. (July 2015) - Morandi, E.; Monteleone, M.; Merlini, D.A.; Vignati, G.; D'Aponte, T.; Castoldi, M.; Bani, M.R.; Giavazzi, R.
Abstract : Background: Pancreatic ductal adenocarcinoma is a lethal disease that remains one of the most resistant to traditional therapies. Despite advances in the understanding of the molecular mechanisms underlying pancreatic carcinogenesis, current systemic treatments offer only a modest benefit in symptom control and survival. Methods: The aim of our study was to develop a panel of patient-derived pancreatic ductal adenocarcinoma xenografts that mimic the biological heterogeneity of human pancreatic cancer. 12 patients with pancreatic ductal adenocarcinoma underwent cephalic duodenopancreatectomy. Pancreatic ductal adenocarcinoma xenografts were transplanted, subcutaneously and directly into the pancreas, in SCID mice. Three xenografts (HUPA 4, 8 and 11) took root successfully and were established in pancreas and subcutaneously in the mice. Each mouse was treated with nab-paclitaxel and gemcitabine, given at the optimal dose (intravenous nab-paclitaxel [25 mg/kg] and intravenous gemcitacbine [150 mg/kg]) comparable to the human dosing regimen. Each tumour was then analysed by our pathologist. Findings: Pancreatic xenografts were histologically and pharmacologically similar to the corresponding patient's tumour. Each tumour showed desmoplastic stroma, rare mucosal glandular component, and resistance to combined therapy. Each tumour had a medium time of latency (time to reach 150 mm 3 ) of 50–60 days, a time to reach 250 mm 3 of 60–70 days, and a doubling time of 20 days. Interpretation: This biobank of patient-derived pancreatic ductal adenocarcinoma xenografts could be useful to study the biology of pancreatic ductal adenocarcinoma and develop new treatments.